Fenología reproductiva y anatomía floral de las plantas Aloe vera y Aloe saponaria (Aloaceae) en Cumaná, Venezuela - Velásquez Arenas, Róger (2008)
The reproductive phenology and the floral anatomy of two species of Aloekept under nursery conditions were analized in eastern Venezuela from September 2001 to September 2002. A. vera flowered between December and May; A. saponaria from November through August. In both species, the anthesis lasted 48 h., the anther dehiscence coincided with the opening of the perianth, the stigma receptivity was higher on the second day of anthesis and nectar production reached 0.34 ml/flower. In A. vera 228±77 yellow flowers on long scapes of 76±11 cm and with 1 – 3 shafts were observed; A. saponaria had 94 ± 33 orange flowers on more compact scapes with 3–5 shafts. The pollen/ovule ratio was 4 115.2 in A. vera and 3 247.1 in A. saponaria, thus they can be classified as compulsory xenogams. Frequent visits of Apis mellifera, Trigona sp., Poliste sp., Eumenes sp., Vespa sp., Leucippus fallax and Amazilia tobaci were recorded. Although both species showed a high production of pollen and nectar, and the presence of potential pollinators, by the end of the flowering period, fruits were only observed in A. saponaria, with a 12 % reproductive efficiency. Coupled with the stigmatic receptivity results and the preliminary intra and interspecific crossing experiments, this suggests the existence of protandry and self-incompatibility as reproductive barriers reducing endogamy in these species.